Treatment resistance in schizophrenia and depression as an interactive kind: Mapping the development of a classification through Meta-Narrative review - Leighton Schreyer; Csilla Kalocsai; Oshan Fernando; Melanie Anderson; Vanessa Lockwood; Sophie Soklaridis; Gary Remington; Araba Chintoh; Suze Berkhout (SSM - Mental Health)
Despite ongoing attempts to delineate and name treatment resistance (TR) in psychiatry, the term is increasingly deployed across diagnostic categories. Still, what it is that constitutes TR remains unclear and in flux. Through a meta-narrative review, we construct a sociohistorical map of the concept of TR as it is employed in schizophrenia (TRS) and major depressive disorders (TRD). We track debates about TR, identify underlying assumptions and influencing factors that shape how the concept has evolved over time, and consider the intended and unintended consequences of its conceptualization. We develop our findings as three unique threads that, braided together, offer insight into TR as an interactive kind. Each thread analyzes and plays with the notion of heterogeneity, which arises in the literature as both a theme and a problem to be solved. Thread one looks at prevailing controversies surrounding the definition of TR. Here, heterogeneity arises in relation to how TR is delineated. We also consider the notion of “pseudoresistance,” a novel concept that functions to manage and contain heterogeneity, defining the boundaries of TR through its exclusions. Thread two explores the range of actors whose interests and practices are coordinated to shape TR as a concept: the pharmaceutical industry, academic psychiatry, clinicians, and health systems. Each group has its own interests and orientations: a heterogenous range of actors contributing to the thing that TR is. Thread three examines the intended and unintended consequences that attempts to conceptualize TR have yielded, including a reification of the biomedical paradigm and the personification of TR. This paper offers a systematic approach to thinking about similarities, differences, particularities and tensions embedded within TR to understand the politics and possibilities of the concept.